Elaboração e apresentação de componente curricular integrativo e transversal: uma experiência no contexto da educação alimentar e nutricional para o ensino médio - Solange Azevedo Corrêa (2020)
The National Common Curricular Base (BNCC), a normative document, is the reference for formulários of curricular and pedagogical proposals in the stages and modalities of Basic Education. Contemporary themes, such as Food and Nutritional Education (FNE), are covered in the BNCC. FNE is a field of knowledge and continuous practice which promotes healthy and adequate eating habits. Educational actions are important for the construction of new knowledge, values and attitudes for the development of adolescents, aligned with the human right to adequate food and the guarantee of food and nutritional security. The objective of this paper was to elaborate a proposal of an elective curriculum component aligned with the curricular guidelines and the current legislation for High School, with the FNE theme in the school context, using an integrative, investigative, interdisciplinary and transversal approach. The action-research methodology was presented in the trajectory of this work, and it is a descriptive study related to eating habits and practices of adolescents from the 2nd and 3rd years of high school, aged 15 to 18, from a public state school in Belo Horizonte. It was adopted as theoretical reference the “Reference Landmark of Food and Nutrition Education for Public Policies” and the “Dietary Guideline for the Brazilian Population” to the concepts about characteristics and determinants of adequate and healthy eating habits. In the education, it was adopted the “Praxis and the Sequence of Investigative Teaching”, aligned to the BNCC and the principles of the ‘Reference Landmark of Food and Nutrition Education for Public Policies”. Data and information about eating habits and knowledge about food and the student’s eating practices were obtained through a questionnaire of multiple choice questions and essay questions. Answers from 14 students were obtained. Students with heterogeneous knowledge and from various social, economical and cultural classes. From the diagnosis it was possible to comprehend how the students understand healthy eating and its frequency. These information subsidized the proposal of the curriculum component. It was made evident the need to broaden the concepts of food and nutrition in an interdisciplinary way: the human right to adequate food and the food and nutritional security; classification of food according to its processing; historical, social and cultural aspects of eating; eating system and contemporary themes about eating. Thus, it was proposed the planning of an elective subject which reflected coherent teaching and learning regarding the nowadays discussions in the field of food and nutritional education. This accomplishment was due to the opportunity of the continuing education for teachers, which made it possible the formulation and insertion of the FNE theme in High School. This paper created instruments, according to the applicable laws, which contribute to the construction of knowledge, skills, attitudes and values to the formulations and implementation of the formative component of the flexible part of the BNCC, as well as the technical -scientifical basis in order to educate the different actors of education to support the inclusion of this proposal in the Political Pedagogical Project of High Schools.